2011
DOI: 10.3171/2010.9.jns10368
|View full text |Cite
|
Sign up to set email alerts
|

Progressive aneurysm development following hemodynamic insult

Abstract: Hemodynamic insult can elicit a pathological vascular response leading to a self-sustaining aneurysmal remodeling that does not require persistence of the original inciting factor to continue its pathological progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 45 publications
5
94
0
Order By: Relevance
“…This is consistent with reports of IA initiation at the BT after both BCCA-L [20][21][22]24 and unilateral CCA ligation. 20,23 Specifically, Meng et al 22 found that the aneurysmal development at the BT continued out to 6 months, even after normalization of the inciting WSS and cessation of adaptive remodeling at 4 to 5 weeks. By comparing the 5-day and 6-month groups in the current study, we also found that the pathologic changes throughout the CoW increased with time.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with reports of IA initiation at the BT after both BCCA-L [20][21][22]24 and unilateral CCA ligation. 20,23 Specifically, Meng et al 22 found that the aneurysmal development at the BT continued out to 6 months, even after normalization of the inciting WSS and cessation of adaptive remodeling at 4 to 5 weeks. By comparing the 5-day and 6-month groups in the current study, we also found that the pathologic changes throughout the CoW increased with time.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies of BT aneurysm formation in the same model (rabbit BCCA-L) have demonstrated that aneurysmal remodeling is a maladaptive response to elevated hemodynamic stresses. 22,24 Through detailed hemodynamics-histology mapping, we found that IA initiation at the BT (defined by regions of IEL loss) was associated with high WSS combined with positive WSS gradient above a threshold. 24,33 This hemodynamic condition, often associated with bifurcation apices, 34 has been recognized to independently cause de novo IA formation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…5,6 CFD offers an excellent alternative for testing hypotheses statistically by correlating hemodynamic variables and aneurysm rupture by using clinical data. Correlation does not imply causation, but different causative mechanisms lead to different correlations that can be tested by combining hemodynamic models (computational or not) and clinical data.…”
Section: Why There Are a Large Number Of Parameters Publishedmentioning
confidence: 99%